Assessment of obesity in the Indian setting: A clinical review - K.G. Sruthi; Sushil Mathew John; Sam Marconi David (Elsevier, 2023)
Background: Obesity is an important public health concern, one of the main lifestyle illnesses leading to chronic diseases like metabolic syndrome, diabetes, cardiovascular diseases, cancers, depression, and stroke. Hence diagnosis and management of obesity as early as possible are essential to prevent the development of these diseases. The present paper reviews some of the key indicators useful in the assessment of obesity. Methods: We collected and reviewed different articles on obesity. Conclusion: Obesity is a serious non-communicable disease associated with multiple risk factors leading to multiple chronic diseases. Early identification for management is essential to reduce the risk factors of the disease. Proper diet and adequate physical activity should be followed regularly to combat the condition. For diet, eating on time, eating healthy fruits and vegetables, and avoiding junk and processed foods would be healthy and Physical activity of 30 min a day is recommended for all individuals to prevent obesity in the future.